Identificação dos problemas de sexualidade, DST, AIDS e drogas com diretores de escolas de 1° e 2° graus: contribuição de uma pesquisa-ação nessa área - Bueno, Sônia Maria Virella (Brazilian Journal of Sexually Transmitted Diseases, 1997)
The research of the opinions of 1° and 2° grade schools directors were collected by know. The difficulties related the general problems of student's integral sexual health developing in conjunction with the educationa/ actions and training them attend properly the present claims related with safe, sexuality, STD/ AIDS, anddrugs in their professional place. lnspite of the interviews had the knowledge of the problems in their working local, they are not ready to resolve the questions about sexuality, STD/AIDS, and drugs, demonstrating difficulties, fears, and worries. Therefore, carry-out researchs in this area is urgent and go the instruction of people to work tbese themes in schools.